2018
DOI: 10.1039/c8ra02461h
|View full text |Cite
|
Sign up to set email alerts
|

Ni–Al–Cr superalloy as high temperature cathode current collector for advanced thin film Li batteries

Abstract: To obtain full advantage of state-of-the-art solid-state lithium-based batteries, produced by sequential deposition of high voltage cathodes and promising oxide-based electrolytes, the current collector must withstand high temperatures (>600 C) in oxygen atmosphere. This imposes severe restrictions on the choice of materials for the first layer, usually the cathode current collector. It not only must be electrochemically stable at high voltage, but also remain conductive upon deposition and annealing of the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 61 publications
(70 reference statements)
0
19
0
Order By: Relevance
“…Li et al used platinum (Pt) on aluminum (Al) as substrate. Further studies with Pt, 19,20 gold 21,22 (Au), stainless-steel 23 (StSt) or metal alloy 24 substrates have been published and show similar behaviour. 15 Komaba et al reported a relationship between the temperature of the crystallization process and the cycling performance of LMO thin-layers on a StSt substrate.…”
Section: Introductionmentioning
confidence: 77%
“…Li et al used platinum (Pt) on aluminum (Al) as substrate. Further studies with Pt, 19,20 gold 21,22 (Au), stainless-steel 23 (StSt) or metal alloy 24 substrates have been published and show similar behaviour. 15 Komaba et al reported a relationship between the temperature of the crystallization process and the cycling performance of LMO thin-layers on a StSt substrate.…”
Section: Introductionmentioning
confidence: 77%
“…Due to the high reactivity of the precursor compounds and the high processing temperatures, the use of a metallic back contact is unfeasible as non‐conductive phases are formed at the interface. Several experiments with different back contacts (Pt, Au, Ta, TiN, Ni‐Al‐Cr [ 34 ] ) were carried out resulting in all cases in highly resistive interfaces. We employed therefore the above‐mentioned in‐plane architecture, which is widely used to characterize conductivities in thin films.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is frequently observed that high‐temperature processing facilitates “cross‐talk” between the electrode and solid–electrolyte, essentially leading to element exchange or interphase formation at the electrode/SE interface. [ 131,132 ] With combined thermal analysis strategies and first‐principles calculations, Miara et al. studied the chemical compatibility between three high‐voltage spinel cathode materials (Li 2 NiMn 3 O 8 , Li 2 FeMn 3 O 8 , and LiCoMnO 4 ) and two solid–electrolyte materials (Li 1.5 Al 0.5 Ti 1.5 (PO 4 ) 3 and Li 6.6 La 3 Zr 1.6 Ta 0.4 O 12 ) materials during co‐sintering.…”
Section: Interface Challenges and Tailoring Strategiesmentioning
confidence: 99%